IDENTIFICATION OF TREATED-COLOR FRESHWATER CULTURED PEARLS - Karampelas, S.; Fritsch, E.; Sklavounos, S.; Soldatos, T. (Bulletin of the Geological Society of Greece, 2007)
Demand for colored pearls has grown during the last thirty years. Colored pearls are rarer than white ones. Thus treated-color pearls have entered the marketplace and their identification became a challenge for the gemologists. With only the help of visual observation, EDXRF and X-radiography, methods that are used today for pearls identification, it is not always easy to identify them. Previous studies, have established that Raman scattering is useful to detect pigments in cultured freshwater pearls. The present study is based on the measurement of the Raman spectroscopy of 35 natural colored freshwater pearls and 15 treated-color freshwater pearls, covering a wide range of typical colors for this material, with green excitation. All natural- color pearls show the two major Raman resonance features of polacetyenic pigments assigned to C=C stretching-at about 1530(±25) cm'1- and C-C stretching - at about 1130(±10) cm' -, regardless of their specific hue. In this paper it is proposed that the absence of these Raman features prove the artificial origin of pigments in a colored freshwater cultured pearl.